(3OQhS aj GdeMGSHI GdeYebI MSH GdfXGe GdeMGSHj GdeGdj (B(SCF) :s (3ehLg dWdHI Ydhe GdJSjjQ hGdYdhe GdJLGQjI hGdcdHI GdegJejf HGdeMGSHI hGdeeGQSjf (B/s - (3HcGQj, HdNjQs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2016)
(3jJfGhd GdcJGH GdeYfhf H` OQhS aj GdeMGSHI GdeYebI MSH GdfXGe GdeMGSHj GdeGdj (B(SCF)(3, ceMhQ Chd eONd dCge HfhO GdfXGe GdeMGSHj GdeGdj heHGOF haQhV GdeMGSHI, CeG GdKGfj ajTed OQGSI GdJKHjJGJ GdYjfjI hGdeYfhjI hGdeGdjI hYbhO GdEjLGQ GdJehjdjI HGdEVGaI Edi GdGgJdGcGJ hNSGFQ GdbjeI hGdJfGRd Yf GdJKHjJGJ , aj Mjf NUU GdeMhQ GdKGdK dOQGSI GdeNRhfGJ hjJYdb HbhGYO Jbjje GdeNRhfGJ hGdbjhO GdeMGSHjI GdeJYdbI HgG hGdeYGdLI hab GdLQO GdeJfGhH hJbjje GdeNRhfGJ aj fgGjI GdOhQI HGdEVGaI Gdi YedjI GdLQO GdeGOj, CeG GdeMhQ GdQGHY ajMJhi Ydi OQGSI MSGHGJ QDhS GdCehGd hjQJHW HGdJWQb Edi LejY MSGHGJ GdeLehYI GdChdi , GdNGeS (B: (3GdeDhhfGJ hjJYdb HTQhW Jchjf GdeDhfI heNJda MSGHGJgG, hbO JfGhd GdeMhQ GdSGOS MGdI GdebGQHI GdHfcjI IjJYdb HCgejJgG heQGMd ELQGFgG, CeG GdSGHY abO NUU ddYbhO WhjdI GdCLd hjVe cd ef JYQjagG hJMOjO JcGdja hEjQGOGJ GdYbhO WhjdI GdCLd HGdEVGaI Gdi GdeYGdLI GdeMGSHjI dgG(B.s
(3GdeQGLY U(B.285s
Keywords: (3GdfXGe GdeMGSHj GdeGdj (B- (3GdLRGFQs; (3GdeMGSHI GdeYebIs